The antecedents of cloud computing adoption and its consequences for MSMEs' performance: A model based on the Technology-Organization-Environment (TOE) framework - Frank Aligarh; Bambang Sutopo; Wahyu Widarjo (Cogent Business & Management, 2023)
The utilization of cloud computing technology by Micro, Small and Medium Enterprises (MSMEs) businesses has become increasingly widespread. The reason for this trend is the relatively low cost in comparison to the benefits derived, which has led to a continued adoption of cloud computing. Consistent with this, the objective of this study is to investigate the factors that influence the adoption of cloud computing and its impact on MSMEs performance. An integrated model was developed based on the Technology-Organization-Environment (TOE) framework, which combines the elements of cloud computing adoption and micro and small business enterprise performance into a single model. The data for this study was obtained through a structured survey questionnaire administered to 197 owners/managers of MSMEs in Indonesia. The results obtained through SEM-PLS analysis indicate that factors such as relative advantage, organizational readiness, bandwagon effect, competitor pressure, computer self-efficacy, and computer anxiety significantly influence the adoption of cloud computing. However, the factors of complexity and top management support were found to have no significant effect on cloud computing adoption. This research provides a theoretical contribution to the expansion of the TOE Framework.
Keywords: 650; Indonesia; cloud computing adoption; MSMEs performance; TOE